A Simple Method to Create Gamma-ray-source Spectrum for Passive Gamma Technique. (December 2017) - Shiba, Tomooki; Maeda, Shigetaka; Sagara, Hiroshi; Ishimi, Akihiro; Tomikawa, Hirofumi
Abstract: A simple but sufficiently accurate method for constructing a gamma-ray source for photon-transportation calculations is developed for canisters containing fuel debris from the Fukushima Daiichi nuclear power plant. The new method couples a baseline spectrum evaluated using the ORIGEN2 code with a line spectrum obtained from fission products (FPs) of interest. One of the advantages of the method is its ability to take bremsstrahlung X rays into consideration using the bremsstrahlung libraries of ORIGEN2. The new gamma-ray source is used to calculate the response of a high-purity germanium (HPGe) detector, and these results are compared with a benchmark test of experimental measurements of irradiated fuel pins. The shape of the simulated gamma-ray spectrum agrees well with that of the spectrum obtained by experiment. Moreover, bremsstrahlung X rays are confirmed to have little effect on spectrum shape formation because the baseline gamma-ray spectrum is mainly formed by Compton scattering of strong gamma rays from FPs such as Cs-137 and Eu-154. Gamma-ray source data are created for a debris composition recently evaluated at JAEA, and subsequent photon-transportation calculation is performed to evaluate the leakage gamma-ray spectra from a canister containing fuel debris for nuclear-material-accountancy purposes.